Pathogens in Nosocomial Infections: Epidemiology, Resistance, and Control Measures - Tahseen Khan (International Journal of Pathogens, 2025)
Nosocomial infections, also known as healthcare-associated infections (HAIs), are a serious global health issue, leading to higher patient morbidity, prolonged hospital stays, and increased medical costs. Various pathogens—such as bacteria, viruses, fungi, and parasites—are responsible for these infections, especially in healthcare environments where they easily spread. They can be transmitted through direct contact with infected patients, contaminated medical equipment, or even airborne particles.Patients with weakened immune systems, those requiring prolonged hospitalization, and individuals using invasive devices like catheters and ventilators are especially vulnerable. One of the biggest challenges in treating HAIs is the growing problem of antimicrobial resistance (AMR). Pathogens such as Methicillin-resistant Staphylococcus aureus (MRSA) and Carbapenem- resistant Enterobacteriaceae (CRE) have developed resistance mechanisms like beta-lactamase production, efflux pumps, biofilm formation, and genetic mutations that make antibiotics less effective. The overuse and misuse of antibiotics in hospitals further accelerate this resistance, leaving fewer treatment options and increasing the risk of complications. To prevent healthcare-associated infections (HAIs), medical facilities need to enforce strict infection control practices. This includes thorough hand hygiene, responsible use of antibiotics, regular monitoring for infections, and proper sterilization of medical tools and equipment.Isolation protocols and environmental disinfection also play a key role. Additionally, researchers are exploring innovative treatments like bacteriophage therapy and probiotics. A team-based approach involving medical staff, microbiologists, and public health officials is essential to effectively prevent and manage HAIs.
Keywords: Antimicrobial resistance (AMR); Healthcare-associated infections (HAIs); Infection control measures; Methicillin-resistant Staphylococcus aureus (MRSA); Nosocomial infections